Luminosity and trascendence of Mexican Revolution's narrative. José Rubén Romero's work - Ceballos Garibay, Héctor (Cultura y Representaciones Sociales, 2011)
The novel of the Mexican Revolution constitutes, as well as the Mexican mural movement, one of the most valuable aesthetic contributions of our country to universal culture. In addition, it not only constitutes a milestone for the history of national and world literature, but it also represents a lofty contribution to the historical knowledge of the period (1910-1940) and a sociological and anthropologic array of great importance for the comprehension of the diverse idiosyncrasies that characterized the Mexican nation during the first half of the 20th century. In fact, the set of works that integrate the NRM offers us a lucid recreation, both testimonial and artistic, of multiple real or fictitious scenes across which its writers project an enlightening light on the social and political structures that were annihilated and emerged in that convulsed time, the ancient and new conflicts, regional and national problematic, the justice ideologies and the personal ambitions, the atavistic mentalities and the behavioral transformations of the masses and the elites, as well as the context of destruction and renovation inherent to the stages of the armed fight and the post revolution. This enormous literary and documentary wealth is the factor that helps to explain why the NRM must be conceived as s suitable frame for any contemporary review of Jose Rubén Romero’s narrative work, a writer whose novels not only reveal a sharp and rebellious spirit, but also represent an accurate critical X-ray photography of the Mexican prevailing society at the dawn of last century.